Cover Image, Volume 2, Issue 3. Issue 3 (19th June 2019) - Unknown
Polymer Crystallization Research in China: In article e10008, Xi‐Xi Zhang and colleagues studied the formation of shish‐kebabs induced by flow under pressure in a binary blend of long‐ and short‐chain polyethylene. The results of their experiments indicated a synergetic effect between pressure and long‐chain on the formation of shish‐kebab after flow. Under pressure, flow‐induced oriented chains or chain segments were greatly reserved, without fast relaxation. The probability of these oriented microstructures to develop into shishes was elevated by pressure, especially for long chains with natural slower reptation dynamics. Therefore, shish‐kebab structures would be generated by flow easily with the coexistence of high pressure and long polymer chains. (DOI:10.1002/pcr2.10059 )